Cost of hospitalization for ischaemic heart and cerebrovascular diseases in Belgium. (20th October 2021) - Gorasso, V; Vandevijvere, S; Van der Heyden, J; De Bacquer, D; Devleesschauwer, B; De Smedt, D
Abstract: Background: Cardiovascular diseases (CVDs) are the leading cause of global mortality and a major contributor to disability. According to European Cardiovascular Disease Statistics, in 2017 there were 108.7 million people living with CVDs in Europe resulting in about 4, 681 disability-adjusted life years per 100, 000 inhabitants. Among these, ischaemic heart and cerebrovascular diseases (IH&CBD) represent the highest burden in terms of morbidity, mortality and health care costs. CVDs were estimated to cost the EU €210 billion a year, where 28% was attributable to IH. The aim of this study was to assess the financial burden at societal level of IH&CBD in Belgium based on hospital discharge data, considering that inpatient hospital care costs accounted for about 51% of the total healthcare costs in CVDs. Methods: IH&CBD were identified based on ICD-10 codes following the definition provided in the Global Burden of Disease study in 2017. IH: angina pectoris (AP) I20 and I25, acute myocardial infarction (AMI) I21-I24; CBD I60-I68. Mean annual number of patients and direct hospitalization costs from 2016 to 2018 were retrieved from the Belgian hospital discharge dataset, considering both primary and secondary diagnoses. Results: Within the observed diseases, AP was the most common reason for hospitalizations with an average of 41, 439 hospitalized patients per year. Yearly, 27, 630 patients were hospitalized for CBD and 14, 928 patients were hospitalized for AMI. The yearly hospitalization cost for AP and AMI in Belgium was on average respectively €219, 688, 254 and €133, 343, 881. CBDs accounted for the largest direct hospitalization cost with €301, 900, 539 per year. Conclusions: In Belgium, on average almost 84, 000 people are hospitalized yearly due to IH&CBD; On average, Belgium spends around €655 million a year for these hospitalizations. Key messages: IH&CBD represent a high health and financial burden in Belgium. Since IH&CBD can be linked to several behavioral risk factors, this burden could be reduced with target health interventions.